Experiences in animal breeding of Cuniculus paca as a contribution to their conservation and sustainable use in Meta Department (Revista Sistemas de Producción Agroecológicos, 2013)
The Cuniculus paca is a species that has been most widely used in Colombia along its history, because it has a great adaptation to adverse conditions, maintaining good meat production. Due to decreased some population barnacle and increasing populations subjected to confinement, the researchers have raised to generate information about behavior of the species from captive individuals, so they were made different use and rearing practices alternatives as input the conservation of the species, in order to generate economic benefits, taking advantage of the characteristics of C. paca. From the visit to four cores relocation and Merecure Ecozoo Park for two months, the researchers obtained information about the reproductive biology of this specie, characteristics of the captive population and ex situ rearing. This information about their habitat and in captivity was used to propose different alternatives handling and use. To involve all components rearing practices of wildlife, obtaining an approximation to the perception of people about of these alternatives of use. For this reason, we created a manual on animal breeding of C. paca. The captive population is predominantly young adulthood, because their mortality rate is low. Females have their first estrus after six months old of age; the average obtained is 116 gestation days although it is low in comparison to other populations implies a slow growth. Furthermore, there is a tendency to seasonality in the reproductive process, while females reach mostly have two deliveries per year, but this fails because captive individuals are not suitable for reintroduction of wildlife species programs, so Therefore, it is necessary to raise C. paca breeding programs in captivity marking individuals for a proper follow-up. Also analyzed using alternatives such as ecotourism, exhibition in zoos, animal breeding for meat production, and the researchers conclude that it is important to promote the sustainable use of C. paca considering its favorable characteristics for a productive animal breeding.
Keywords: Cuniculus paca; captivity; animal breeding; wildlife